Kompensasi dan Hubungan Kerja: Kajian Strategis dalam Konteks Organisasi Modern - Dewi, Mawar Kumala; Aisah, Dewi Nur; Yunizar, Putri; Safina, Wan Dian (Universitas Medan Area, 2025)
This research aims to strategically examine the role of compensation and employment relations in the context of modern organizations. In the midst of the dynamics of globalization, technological developments, and the diversity of workforce generations, compensation is an important factor in increasing employee motivation, satisfaction, and loyalty. This study uses a qualitative approach with a literature study method. The main sources of information in this study include relevant literature, such as books, articles from journals, papers presented in conferences, and other references related to the subject under study. related to the subject under study to identify trends, challenges, and opportunities in compensation and labor relations management. The results of the study show that a fair and innovative compensation system and effective cross-generational communication are key in improving overall organizational performance. On the other hand, a healthy working relationship, based on a legally valid agreement, is an important foundation for creating a harmonious and productive working climate. and productive work climate. In a multigenerational and multicultural work environment, The effectiveness of communication and understanding of intergenerational expectations and values are also crucial aspects that affect the sustainability of working relationships.